PENGARUH KOMPETENSI PERSONAL GURU DAN IKLIM SEKOLAH TERHADAP ISLAMIC WORLDVIEW SISWA DI MAN 2 BOGOR - Tantowi, Hilman (Tawazun: Jurnal Pendidikan Islam, 2019)
To produce qualified graduates, learning activities in schools should be supported by factors such as quality education support, curriculum, infrastructure, learning media, performance, cooperation, good management and competent human resources of teachers who have good competence , good teacher competence has a role in improving school climate and in turn is able to cultivate student worldview. Each student both individually and in groups will have a worldview where every belief, nation, civilization and even everyone has their own worldview, by taking on a certain worldview the order of human life is experiencing differences with each other. The emergence of worldview influenced by several factors, while the dominant factor is the belief system, culture, religion, philosophy, the order of values and much more.